Hydration levels of the body as measured by bioelectrical impedance. - Grieve, Clayton Lance (My University, 1994)
This study considered the influence of the free electrolytes in the total body water on the electrical properties of the body. Using a model of slightly dehydrated and then rehydrated volunteer s, the electrolyte concentration and total body water volume were measured and compared with electrical impedance (Z) measurements of the body. (Abbreviation abstract)
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy
Keywords: Bioelectrochemistry.; Impedance, Bioelectric.; Body fluids -- Measurement.; Body composition.; Water-electrolyte balance (Physiology); Water-electrolyte imbalances.; Water in the body.